Building the data-driven law firm. (2021) - Curle, David; Hamilton, Thomas; Urban, Holly; Crews, Aaron; Chan, Edward; Roberts, Jennifer; Millard, Robert; Frears, Joanne; Drane, Simon
No abstract available